Communication: Dynamic Data System Modeling—Revisited - Steudel, H. J.; Wu, S. M. (Management Science, 1978)
In his comments on our paper, “A Time Series Approach to Queueing Systems with Applications for Modeling Job-Shop In-process Inventories,” Management Sci., March 1977, Oliver D. Anderson points out an inadequacy in the modeling results we presented on pp. 748–748. As a defender of the faith, he suggests that the culprit is our modeling strategy, a procedure he views as a Black-Box heresy. Since our modeling strategy is quite new and relatively unknown, especially compared to the Box-Jenkins (1) approach, Anderson's concluding remarks are not surprising.